Dạy học giải các bài toán chủ đề “Đạo hàm” (Toán 11) nhằm phát triển năng lực giải quyết vấn đề toán học cho học sinh - Nguyễn, Ái Quốc; Trương, Hải Châu; Trần, Liễu Đại Phúc (Tạp chí Giáo dục, 2025)
Competency-based teaching is a modern teaching trend, responding to the requirements of teaching innovation in the current context. According to the 2018 Mathematics General Education Curriculum, the competency to solve mathematical problems is one of the five core mathematical competencies to develop for students. Based on existing scholarship, the study proposes a process for solving mathematical problems with illustration through the topic “Derivatives” (Math 11) to develop students’ math problems solving competency. The teaching experiment was conducted in a Grade 11 class in Tay Ninh Province, Vietnam. The results of the teaching experiment showed that the students actively participated in the classroom activities, and were able to use derivative knowledge to solve problems related to derivatives. To assess the development of students’ mathematical problem-solving competency, we used qualitative and quantitative methods when analyzing the groups’ work.